2001
DOI: 10.2307/3871150
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling Allows Comprehensive Phenotyping of Genetically or Environmentally Modified Plant Systems

Abstract: Metabolic profiling using gas chromatography-mass spectrometry technologies is a technique whose potential in the field of functional genomics is largely untapped. To demonstrate the general usefulness of this technique, we applied to diverse plant genotypes a recently developed profiling protocol that allows detection of a wide range of hydrophilic metabolites within a single chromatographic run. For this purpose, we chose four independent potato genotypes characterized by modifications in sucrose metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
271
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(281 citation statements)
references
References 41 publications
8
271
1
1
Order By: Relevance
“…Derivatization was performed according to recognized protocols [8]. Dried extracts were reconstituted in 10 mL of a 40 mg/mL solution of methoxyamine hydrochloride in pyridine and heated for 90 min at 301C.…”
Section: Derivatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Derivatization was performed according to recognized protocols [8]. Dried extracts were reconstituted in 10 mL of a 40 mg/mL solution of methoxyamine hydrochloride in pyridine and heated for 90 min at 301C.…”
Section: Derivatizationmentioning
confidence: 99%
“…Other investigators have differentiated hop varieties by using analysis of hop acids or flavonoids using reversed phase HPLC [2]. In 2001 Roessner et al showed that profiling metabolites in plant extracts allows comprehensive phenotyping of genetically or environmentally modified plant systems [8]. Such studies draw on simple extraction procedures that have been shown to be very robust [9] and have permitted wide-ranging high-throughput applications, such as phenotyping to diagnostic analyses in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of losing information in the process of averaging metabolite levels, each metabolite profile represents a true and valid response of metabolism upon subtle (but unknown) changes in parameters of the system. By computing correlation coefficients of metabolite-metabolite plots, the detection of homeostatic regulation of metabolite ratios could be set onto a more rigid statistical basis (Arkin et al, 1997;Roessner et al, 2001;Kose et al, 2001). A computation of metabolic models based on a combination of co-response MCA theory and experimentally detected metabolomic correlations, however, remains to be shown.…”
Section: Modelling Based On Metabolic Flux Measurementsmentioning
confidence: 99%
“…If this is not the case, the data acquisition might have been obscured by either sample preparation faults or low analytical precision during data acquisition. Eventually, subtle mutations that result in silent phenotypes might not render a clear clustering result by any common means such as principal component analysis (Fiehn et al, 2000b;Roessner et al, 2001) or discriminatory analysis (Raamsdonk et al, 2001). For such cases, further methods need to be developed that unravel potential differences between the populations being studied.…”
Section: Data Miningmentioning
confidence: 99%
“…Recently, analytical methods such as liquid chromatography-mass spectrometry, gas chromatography-mass spectrometry, nuclear magnetic resonance and capillary electrophoresis-mass spectrometry (CE/MS) provided new insights into the biological function of plant metabolism. [19][20][21][22] Here, using capillary electrophoresis-mass spectrometry (CE/MS), we determined the concentrations of target metabolites in rice suspension cells treated with M. grisea elicitor to facilitate understanding in the early steps of elicitor-induced processes. Overall changes in the metabolite levels in the central pathways were observed.…”
mentioning
confidence: 99%